Exploring the empowerment and motivational factorsof women leaders - Juhász, Tímea; Varga, Erika; Czeglédi, Csilla; Adorján, Krisztián (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2024)
Nowadays, the discourse on women leaders receives special attention because of its impact on social development and organisational success. The topic of the paper is to examine the characteristics, motivational capabilities and decision-making mechanisms of Hungarian female leaders. The study also discusses what incentives, internal or external motivators are necessary for women leaders to achieve their goals. Research questions include what factors can be identified for a woman to become a leader and what characteristics a successful female leader should have. The results of a questionnaire survey of a sample of 228 women managers with different educational backgrounds, different company sizes and different managerial levels show that the factors required to achieve leadership are perceived differently by women managers. The research also reveals that the factors required to achieve leadership are closely related to the factors that motivate women managers